Parametric study of palladium/graphene catalyst on-board steam reformer for hydrogen generation from IC engine’s waste - Rahman, Mohammed Ataur; Kyaw, Myo Aung; Rafia, Afroz (IJENS, 2017)
Climate change is recognized as one of the greatest environmental threats facing the World today and it has long been appreciated by governments that reducing the impact of the IC engine powered motor vehicle has an important part to play in addressing this threat. This article presents the parametric study of a palladium (Pd)/ graphene oxide (GO) catalyst on- board hydrogen generator, which would have targeted function to make the vehicle energy efficient and improve the emission. The optimisation of the concentration of GO and Pd has been conducted with COMSOL software. The gas chromatography analysis on exhaust of a 4-stroke spark ignition engine has been conducted and found that the concentration of exhaust is 0.5% H2, 0.5% CO, 11% CO2, 21% UHC and H2O. The Pd/GO catalyst hydrogen generator is expected to reformate the exhaust gas about 35% H2 (clean fuel), 5% CO, 10% CO2, 5% UHC, and H2O. The enriched and heat-treated 7% of hydrogen is considered to be pumped directly into the engine. It is expected that Pd/GO catalyst hydrogen generator would be able to save the engine fuel consumption about 12% for 1.4 -1.6 litre engine and reduce green house gas (GHG) emission about 40%.